Absorptive capacity: Overview of the evolutionary path of research networks (1976-2020) - Lima, Karina Teixeira; Moreira, Vinicius Farias (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This study analyzes the evolution of scientific publications on absorptive capacity (Absorptive Capacity - ACAP) between 1976-2020 to construct a research panorama. It is a bibliometric study of cocitation analysis using cluster analysis, which was performed using the VOSviewer software. The results show the application of the absorptive capacity to explain organizational phenomena and reviewed the literature to identify its dimensions of achievement: acquisition, assimilation, transformation, and application. There are links between absorptive capacity and innovation, such as investing in Research and Development (R&D) projects as a relevant practice for promoting ACAP, stimulating the acquisition, assimilation, transformation, and exploitation of external knowledge in organizations.